A new dimension in learning badminton refereeing: A 3D simulation android app with virtual reality integration - Gazali, Novri; Cendra, Romi; Efendi, Yoyon; Setiawan, Edi; Medeirosd, Alexandre Igor Araripe; Hamdi, Liwa Ul (Jurnal Keolahragaan, 2024)
Virtual reality (VR) technology has become increasingly popular and widely used in sports environments in higher education, but there are still some challenges that need to be overcome. This research aims to create an Android-based 3D simulation application with the help of virtual reality as a learning tool for badminton refereeing. The methodology used is the Multimedia Development Life Cycle (MDLC). The multimedia development methodology consists of six stages, namely concept, design, material collection, creation, testing, and distribution. This application shows great potential for supporting the development of human resources in the field of badminton sports, both for novice referees and players. However, it should be noted that the current research is still at the application creation stage, with effectiveness and distribution tests still to be conducted. Through the optimisation of rendering techniques, test results show good simulation performance on smartphones with a resolution of 1920 x 1080, although the use of VR Box devices may cause eye fatigue in long-term use. This research makes an important contribution to the development of VR-based learning applications for badminton refereeing, with the hope of improving understanding and skills in sports and becoming the basis for the development of sports education technology. Future research should focus on completing the pending stages as well as expanding insights into user interaction and the positive impact that apps can have